2002
DOI: 10.1097/00007632-200212150-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Asymmetric Laxity of the Sacroiliac Joints in Pregnancy-Related Pelvic Pain

Abstract: These data indicate that in women with moderate to severe complaints of pelvic pain during pregnancy, sacroiliac joint asymmetric laxity measured during pregnancy is predictive of the persistence of moderate to severe pregnancy-related pelvic pain into the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 23 publications
0
71
0
3
Order By: Relevance
“…After screening all titles and abstracts eight studies were found which addressed the inclusion and exclusion criteria [15,[45][46][47][48][49][50][51]. In addition to these, two more articles were found after hand searching [52,53].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening all titles and abstracts eight studies were found which addressed the inclusion and exclusion criteria [15,[45][46][47][48][49][50][51]. In addition to these, two more articles were found after hand searching [52,53].…”
Section: Study Selectionmentioning
confidence: 99%
“…In total, six studies reported the relationship between PPGP and pelvic mobility [15,45,[51][52][53][54] and four studies reported the relationship between motor control and PPGP [47][48][49][50]. Among them, seven were considered as case control [15,45,46,49,50,52,53] and three as cohort studies [47,48,51].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Regarding the postpartum patient, previous research has indicated through a prospective cohort study that in patients with moderate to severe pregnancy-related pelvic pain, sacroiliac joint asymmetry laxity is predictive of persisting complaints postpartum in 77% of women. 33 The implementation of chiropractic care as part of the treatment protocol for the pregnant patient may reduce the likelihood of in utero constraint and its associated risks after parturition. Such care may also prevent or reduce the incidence of common prenatal conditions seen with neurologic and physiological involvement postpartum.…”
Section: Adjustive Procedures Of the Pregnant Patientmentioning
confidence: 99%